Pengaruh Solvabilitas Dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Property Yang Terdaftar Di Bursa Efek Indonesia - Monetarist Butar Butar; Agam Sinaga; Ulinar Sihotang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In general, every company is required to generate maximum profits. The core problem of this research is whether the Debt to Equity Ratio and Current Ratio partially and simultaneously affect Return on Investment in property companies listed on the Indonesia Stock Exchange 2023-2024, covering a population of 71 companies and a sample of 30 selected according to sampling criteria using the purposive sampling method. This research uses a quantitative method, with secondary data types. Data collecction techniques used are library research and observation. The data analysis technique used is multiple linear regressiion analisis using the SPSS program. The results of the study show a regresion eqution Y = 0.343 + 0.196 X1 + 0.030 X2. The resullts of the studi indicate that the Debt to Equity Ratio partially affects Return on Investment (ROI). The Current Ratio partially affects Return on Investment (ROI). The Debt to Equity Ratio and Current Ratio simultaneously affect Return on Investment.